Prognostic utility of 99mTc-MIBI single photon emission computerized tomography myocardial perfusion imaging in patients with ischemia and non-obstructive coronary artery disease - Wang, Xiao-Hui; Li, Meng-Dan; Xie, Fu-Xiang; Liang, Huan; Yang, Lu; Wei, Xiao-Fei; Pang, Hua; Wang, Zheng-Jie; Jing, Xing-Guo (Frontiers in Cardiovascular Medicine, 2023)
Abstract Objective: The aim of our study was to evaluate the prognostic value of gated SPECT MPI in Non-obstructed coronary arteries (INOCA) patients,sought to stratify patients more accurately and thus derive more reliable prognostic information. Materials and methods: In total, 167 patients with INOCA were enrolled. The patients were divided into two groups according to their SSS. Patients were followed-up regularly in terms of major adverse cardiovascular event(MACE), including cardiac death, nonfatal myocardial infarction, stroke, re-hospitalization with angina pectoris, and recurrent angina pectoris. Kaplan-Meier curves and Cox’s proportional hazards models were used to analyze survival and identify predictive factors. Results: Adverse cardiac events occurred in 33 cases (19.8%). The rate of MACE was higher in the summed stress score (SSS) ≥ 4 group than in the SSS 0–3 group (30.1% vs 9.5%, respectively, P = 0.001) and MACE-free survival was lower (annual MACE-free rates of 87.5% vs 96.2%, respectively, P = 0.003). Event-free survival was consistently higher in patients with normal arteries than in those with non-obstructive coronary artery disease (annual MACE-free rates of 96.1% and 88.4%, P = 0.035). When the SSS and the CAG results were combined, patients with normal coronary arteries (SSS 0–3) had the best prognosis and those with non-obstructive coronary artery stenosis (SSS ≥ 4) had the worst. However, the early prognosis of patients with non-obstructive coronary artery disease and SSS of 0–3 was comparable to that of patients with normal coronary arteries and SSS ≥ 4 (annual MACE-free rates of 100%, 94.6%, 93.1%, and 78.2%, respectively). Multivariate Cox’s regression indicated that the SSS (hazard ratio [HR] = 1.126, 95% confidence interval [CI] 1.042–1.217, P = 0.003) and non-obstructive coronary artery disease (HR = 2.559, 95% CI 1.249–5.246, P = 0.01) were predictors of adverse cardiac events. Conclusion: SPECT MPI data were prognostic for INOCA patients, thus identifying groups at high risk. The long-term predictive efficacy of such data exceeded that of CAG data. A combination of the two measures more accurately stratified INOCA patients in terms of risk.